Development of Prototype of Hard Capsule Shell Made from Goatskin Gelatin Using Simplex Lattice Design (SLD) as Optimization Method - Muhammad Irfan Said; Yuny Erwanto; Achmad Fudholi; Effendi Abustam (Buletin Peternakan, 2018)
The objective of this study was to evaluate the application of the use optimization methods of Simplex Lattice Design (SLD) with special cubic models in the preparation formula of hard capsule based on goatskin gelatin. Three types of filler materials have been used in the manufacture of capsule shells, namely MgCO3, tapioca starch (TS) and sago starch (SS). The basic ingredient was uses goatskin gelatin and aquadest as a solvent.  The material formulation was calculated according to Simplex Lattice Design (SLD) using the equations Y = β1 (A) + β2 (B) + β3(C) + β12 (A)(B) + β13 (A)(C) + β23 (B)(C) + β123 (A)(B) (C). Based on these equations obtained seven formulas (three proportions formula 100% each component, three proportional formulas 50%: 50% for the mixture of two components and one formula 33.33% for the mixture of three components). The results obtained data related to the proportion of filler use in a mixture of materials. The superimposed contour plot shows that the proportion of the use of three types of filler (MgCO3: TS: SS) in each mixture are (0.224 part: 0.055 part and 0.721 parts).  Next, after further testing of the formula is then obtained properties of the capsule shell prototype, namely: thickness (0.35 mm), solubility (66.64%), and water vapor transmission rate (WVTR) (0.67 g.H2O.m-2 h-1).  The data obtained that the type of SS filler is the most dominant factor influencing in increasing the thickness and solubility properties of the capsule shell, while the filler TS is the most dominant increase in the nature of WVTR.  The results of the study concluded that the application of the SLD optimization method could be applied in the preparation of hard capsule formulations made from goatskin gelatin with better properties.